TARP Effect on Bank Lending Behaviour: Evidence from the last Financial Crisis - Stefano Puddu; Andreas Waelchli (University of Neuchâtel, Institute of Economic Research (IRENE), 2015)
Using a unique data set based on US commercial banks and county level loan origination for the period 2005-2010, we measure whether banks that benefited from the Troubled Asset Relief Program (TARP) increase small business loan originations. We propose an identification strategy which exploits the ownership structureof bank holding companies. We find that TARP banks provide on average 19% higher small business loan originations than NO TARP banks. The disaggregated data allows us to control for the potential demand side effects. When considering poverty and unemployment rates at a county level we show that TARP is effective only in counties suffering from unemployment. Several robustness checks confirm the main result.
Keywords: C23; E58; G21; G28; 330; TARP; Financial Crisis; Loan provision